How is this possible ?

1,129.1K Views

I can prove why 1 = 2

* Lets say y = x
* Multiply through by x xy = x2
* Subtract y2 from each side xy – y2 = x2 – y2
* Factor each side y(x-y) = (x+y)(x-y)
* Divide both sides by (x-y) y = x+y
* Divide both sides by y y/y = x/y + y/y
* And so… 1 = x/y + 1
* Since x=y, x/y = 1 1 = 1 + 1
* And so… 1 = 2

How is this possible ?

Share
Add Comment

  • 1 Answer(s)

    Step 5 is invalid, because we are dividing by (x-y), and since x=y, we are thus dividing by 0. This is an invalid mathematical operation (division by 0), and so by not following basic mathematical rules

    anikam Expert Answered on 24th August 2015.
    Add Comment
  • Your Answer

    By posting your answer, you agree to the privacy policy and terms of service.
  • More puzzles to try-